The praxis of teaching thinking: a case study about student-teachers' experiences in the Malaysian classrooms - Hussien, Suhailah (Common Ground Publishing, 2009)
This paper presents a case study that was conducted at the Institute of Education, International Islamic University Malaysia, on the teaching of thinking. The aims of the study were to understand the student-teachers’ experience in learning and practicing teaching thinking, and assist them in their own conceptualization of teaching thinking. The paper begins by discussing briefly the development of teaching thinking, thinking skills programs, and an alternative pedagogy to teaching thinking skills that had been introduced in the case study. The paper describes how the case study explored student teachers’ views toward the different approaches in teaching thinking skills, their micro teaching, and their experiences of critical pedagogy. Problems faced by the student-teachers in teaching thinking skills are highlighted, and the conceptualization of an alternative pedagogy is the resolution.